Description of a Zostera marina catalase gene involved in responses to temperature stress - Zang, Yu; Liu, Jiao; Tang, Xue Xi; Zhou, Bin (PeerJ, 2018)
Catalase (CAT) is an antioxidant enzyme that plays a significant role in cellular protection against oxidative damage by degradation of hydrogen peroxide to oxygen and water. In the present study, the complete CAT cDNA sequence of Zostera marina was identified through expressed sequence tags (EST) analysis and the rapid amplification of cDNA ends (RACE) technique. The nucleotide sequence of ZmCAT cDNA consisted of 1,816 bp with a 1,434 bp open reading frame (ORF), encoding a polypeptide of 477 amino acid residues, which possessed significant homology to other known plant CATs. The molecular mass of the predicted protein was 55.3 kDa with an estimated isoelectric point of 6.40. Phylogenetic analysis showed that ZmCAT was closely related to CAT from gramineous species. In response to temperature stress, H2O2 and MDA contents in Z. marina increased significantly with cold stress (<10 °C) and heat stress (>25 °C). ZmCAT expression was significantly upregulated at temperatures from 5 to 10 °C and then gradually downregulated, reaching its lowest expression at 30 °C. Recombinant ZmCAT protein exhibited strong antioxidant activity over a wide temperature range, with the highest rZmCAT activity observed at 25 °C and a higher relative activity retained even with heat stress. All these results indicated that ZmCAT was a member of the plant CAT family and involved in minimizing oxidative damage effects in Z. marina under temperature stress.
Keywords: CAT; Temperature stress; mRNA expression; Enzyme activity